Market Development Initiative for Bondhu Chula in Creating Entrepreneurs: A Case from Kachuai Union, Patiya Upazila, Chattogram (Bangladesh Journal of Public Administration, 2019)
The purpose of the study is to assess the effectiveness of the project, “Market Development Initiativefor Bondhu Chula”. Most people in the rural area of Bangladesh use a traditional cooking device.Biomass is the primary source of energy for cooking devices. The limitations of traditional cookingdevices demand the introduction of Bandhu Chula, which is claimed to be energy efficient andenvironment-friendly. Hence potential entrepreneurs were trained to produce and sell this newdevice. The study employed a qualitative approach. Fourteen stakeholders were interviewed. Thestudy found that users were not aware of this, and the local government representatives were notsensitized. Only 4 per cent of households at Kachuai union of Patiya upazila of Chottogram werefound to use Bondhu chula – a fact, which indicates that the project failed to create entrepreneurs.However, the users, and women, in particular, were found to be happy to use this cooking device as itis less time consuming, energy-efficient, less costly and easy to cook.